Bottom‐Up Growth of Graphene Nanospears and Nanoribbons. (3rd August 2022) - Sun, Haibin; Liu, Fengning; Zhang, Leining; Ko, Kyungmin; McLean, Ben; An, Hao; Kim, Sungkyun; Huang, Ming; Willinger, Marc‐Georg; Ruoff, Rodney S.; Suh, Joonki; Wang, Zhu‐Jun; et al.
Abstract: One dimensional graphene nanostructures are one of the most promising materials for next generation electronics. Here, the chemical vapor depostion growth of graphene nanoribbons (GNRs) and graphene nanospears (GNSs) on a copper surface is reported. The growth of GNRs and GNSs is enabled by a vapor–liquid–solid (VLS) mechanism guided by on‐surface propagation of a liquid Cu‐Si catalyst particle. The slow lateral growth and the fast VLS vertical growth give rise to spear head‐shaped GNSs. In situ observations further confirm that the lateral graphene growth can be completely suppressed and thus GNRs are grown. The synthesized field effect transistor (FET) devices show that the GNRs and GNSs have high carrier mobilities of ≈2000 cm 2 V −1 s −1 . Both FET and Kelvin probe force microscopy measurements confirm that the Fermi levels of the synthesize GNSs shift downward from the wide part to the tip is strongly p ‐doped. These findings yield key insights into the growth mechanism of graphene and open a door for achieving a facile and scalable method of synthesizing free standing GNRs and GNSs and their applications, such as the Fermi‐level tunable devices. Abstract : Controlling the suppression of vapor–solid–solid graphene growth along the width direction of the graphene nanoribbon by tuning the flow of H2 during growth gives rise to a spear head‐shaped graphene that are termed as graphene nanospears.